Comprehensive Census and Complete Characterization of Nearby Debris Disk Stars. Issue Volume 10:Issue S314(2015) (November 2015) - Cotten, Tara H.; Song, Inseok
Abstract: Debris disks are intimately linked to planetary system evolution since the rocky material surrounding the host stars is believed to be due to secondary generation from the collisions of planetesimals. With the conclusion and lack of future large scale infrared excess survey missions, it is time to summarize the history of using excess emission in the infrared as a tracer of debris and exploit all available data as well as provide a comprehensive study of the parameters of these important objects. We have compiled a catalog of infrared excess stars from peer-reviewed articles and performed an extensive search for new debris disks by cross-correlating the Tycho-2 and AllWISE catalogs. This study will conclude following the thorough examination of each debris disk star's parameters obtained through high-resolution spectroscopy at various facilities which is currently ongoing. We will maintain a webpage (www.debrisdisks.org ) devoted to these infrared excess sources and provide various resources related to our catalog creation, SED fitting, and data reduction.